Avaliação objetiva de pavimentos flexíveis pelo método do ICP/SHRP. Estudo caso, bairro de Batista Campos em Belém-PA - SOUSA, Talmo Cunha de (2021)
Pavement Management Systems (PMS) are important tools to keep the urban road network in good condition with the minimum use of public resources, but for the PMS to work well it is necessary to evaluate roads surface’s conditions. Therefore, the objective of this research is to survey the condition of the pavement surface in the Batista Campos district. In order to do so, a field survey was carried out based on the SHRP (Strategic Highway Research Program) method and, at the same time, the conditions of horizontal signaling were surveyed. The pavement score was obtained by calculating Pavement Condition Index (PCI), which qualifies the pavement condition from 0 to 100. Among the main results, the average PCI was 86.75 (excellent pavement performance). The district’s arterial roads were better preserved than the collecting and local roads. The most critical stretches had an PCI of 61.67 and the best stretches had an PCI = 100. The most frequent distress were raveling, patching and interference with urban pipes. Most distress detected were classified as low severity and low extension. There was a strong positive linear correlation between the stretch elevations and their respective PCI. Only 48% of the horizontal signs in the district are well preserved, so, the horizontal signs are in worse conservation conditions than the pavements surfaces.